THE RELATIONSHIP BETWEEN PUBLIC EXPENDITURES AND ECONOMIC GROWTH: A PANEL VAR APPROACH - Gökhan Karhan (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Therelationship between public expenditures and economic growth has accelerated,especially after the First World War. In this study, it was investigated usingdata from 1989-2017 for BRICS countries and Turkey for the causality relationbetween public expenditures and economic growth. As a result the causality testshow that there is no causality from public expenditures to economic growth inthe short term but there is causality relationship from economic growth topublic spending. In the long run, it is seen that there is bidirectionalcausality both from public expenditures to economic growth and from economicgrowth to public expenditures.